Waste Disposal in Medical Laboratories: A Comprehensive Review - Dr. Fatma Ibrahim Salama (Journal of Scientific and Human Dimensions, 2026)
Medical laboratories are indispensable to modern healthcare, yet their operations generate a complex array of waste that necessitates meticulous management. This paper provides a comprehensive review of waste disposal practices in medical laboratories, encompassing waste classification, the intricate regulatory landscape, current management strategies, persistent challenges, and emerging sustainable solutions. We categorize laboratory waste into infectious, pathological, sharps, chemical, pharmaceutical, radioactive, and general types, emphasizing the critical role of accurate segregation at the source. The review details the multi-tiered regulatory frameworks, from international guidelines by the World Health Organization to national and local mandates, underscoring the imperative for strict compliance. Management practices, including segregation, collection, secure storage, safe transportation, and various treatment technologies such as autoclaving, microwave irradiation, chemical disinfection, and incineration, are thoroughly examined. Furthermore, the paper addresses significant challenges, including misclassification, inadequate training, high disposal costs, evolving regulations, and the environmental impact of certain treatment methods. Finally, it proposes sustainable solutions and best practices, advocating for waste minimization (Reduce, Reuse, Recycle), enhanced training, adoption of environmentally sound technologies, green procurement, and collaborative partnerships. By synthesizing current knowledge, this review aims to guide laboratory professionals, policymakers, and researchers in optimizing waste management strategies to safeguard public health, ensure occupational safety, and promote environmental sustainability.
Keywords: Medical Laboratories; Modern Healthcare; Waste Disposal; Waste Classification; Waste Minimization